Advanced Manufacturing Techniques for Lightweight Muon Spectrometer Support Structures in the FCC Project - Brajer, Jan; Dub, Martin; Lopot, Frantisek; Maly, Pavel (Manufacturing Technology Journal, 2024)
With the rising demand for efficient, lightweight support structures in high-energy physics experiments, advanced manufacturing techniques and material optimization are key to achieving high-performance designs. This study focuses on the application of generative design and topological optimization in the development of support structures for the FCC muon spectrometer. By leveraging these methods, we maximized material efficiency and minimized weight while ensuring structural integrity and meeting strict design constraints, including non-magnetic properties, minimal deformation, and high precision. A detailed evaluation was conducted with respect to manufacturing techniques that balance perfor-mance with cost-effectiveness, resulting in multiple design iterations of optimized truss configurations. This approach demonstrates the potential of modern manufacturing technologies in enhancing the structural and economic viability of components for large-scale scientific equipment.
Keywords: Additive Manufacturing; Topology Optimization; Generative Design; Muon Chambers; Detector; Frame; FCC